Pengembangan Modul Problem Based Learning pada Materi Asam Basa Kelas XI SMA/MA - Zonalia Fitriza, Meliza Novita Sari, Ellizar, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Generally, in the research method, there are several types of research. The type ofresearch conducted is development research or Research and Development (R & D).This research aims to develop acid-base module based on problem based learning forlearning class XI SMA / MA, and evaluate the categories of validity and practicality ofthe module. The development model used in this development is a 4-D model consistingof 4 stages, namely define, design, development and disseminate. The problem basedlearning acid base module is validated by 5 validators consisting of 3 chemistry lecturersfrom FMIPA UNP and 2 chemistry teachers at SMAN 1 Payakumbuh which usingan instrument in the form of a validation sheet. Practical tests were carried out with 2chemistry teachers and 33 students of class XII IPA 5 SMAN 1 Payakumbuh using instrumentsin the form of practical questionnaires. The results of the analysis of the validity,practicality of the teacher, and the practicality of the students showed that theaverage score of moment kappa (k) was 0.82, 0.88 and 0.80. The module is very validand practical to use.Keywords : Acid Base, 4-D Models, Module, Practicality, Problem Based Learning, Researchand Development (R & D), Validity.